Flaxseed (Linum usitatissimum), Chamomile (Matricariae flos) and Marshmallow (Althaea officinalis) Mouth Rinses in the Therapy of Oral Mucosa Diseases – A Review - Agnieszka Kręgielczak; Magdalena Łukaszewska-Kuska; Agnieszka Mania-Końsko; Barbara Dorocka-Bobkowska (Journal of Natural Fibers, 2023)
Background: Several pathological conditions of oral mucosa are an indication for the use of mouth rinses. Objectives: The aim of this paper is to indicate that herbal oral rinses seem to be a good choice due to their easy accessibility, low cost and simple handling. Methods: The study was based on a literature search of three electronic databases for clinical study or systematic review published until January 2023 exploring the use of selected herbal products in the treatment of oral mucosa diseases. Results: A combination of flaxseed, chamomile and marshmallow can be used to prepare an oral rinse which provides an effective coating, anti-inflammatory and antioxidant effect. It can also be recommended in many pathological conditions such as xerostomia, oral lichen planus, burning mouth syndrome and others because such herbal rinses relieve dryness, burning and pain together with moistening and lubricating effect. Conclusions: Flaxseed, chamomile and marshmallow mouth rinses help to reduce inflammation, promote healing and coating oral mucosa being a beneficial supplement to the daily oral hygiene and treatment procedures.